Innovation Toilet and Barriers of Diffusion in Developing Country Case Study: TOTO Electronic Bidet Seat Toilet - Adhiutama, Akbar; Shinozaki, Michihiko; Yoshikubo, Seiichi (The Asian Journal of Technology Management (AJTM), 2009)
The innovation of electronic bidet seat toilet in Japan has diffused to more than sixty percent of Japanese household while it has low rate of diffusion in other countries especially in developing country. From this phenomenon, it is interesting to understand about the barrier of diffusion, which focuses on the adopter categories of diffusion, barrier factors and proposition of key success factors of the diffusion in Indonesia as one of emerging economic and the member of G 20. There have been few studies about diffusion of innovation toilet, and this paper especially examines the diffusion of new innovations on electronic bidet toilet due to its successful diffusion among Japanese household, and further became a standard fixture toilet in Japan. This paper also discusses the product life cycle of electronic bidet toilet in Japan, global diffusion, identifies adopter categories and barrier factors of diffusion in Indonesia. Finally, theoretical propositions are developed on the diffusion of innovation for electronic bidet toilet in Indonesia.Keywords: Innovation toilet, Barriers of diffusion, Indonesia, TOTO Electronic bidet seat toilet